How systemic inflammation modulates adenosine metabolism and adenosine receptor expression in humans in vivo - Ramakers, Bart P; Wever, Kimberley E; Kox, Matthijs; van den Broek, Petra H; Mbuyi, Faustin; Rongen, Gerard; Masereeuw, Rosalinde; van der Hoeven, Johannes G; Smits, Paul; Riksen, Niels P; Pickkers, Peter (Critical care medicine, 2012)
Adenosine modulates inflammation and prevents associated organ injury by activation of its receptors. During sepsis, the extracellular adenosine concentration increases rapidly, but the underlying mechanism in humans is unknown. We aimed to determine the changes in adenosine metabolism and signaling both in vivo during experimental human endotoxemia and in vitro. We studied subjects participating in three different randomized double-blind placebo-controlled trials. In order to prevent confounding by the different pharmacological interventions in these trials, analyses were performed on data of placebo-treated subjects only. Intensive care research unit at the Radboud University Nijmegen Medical Center. In total, we used material of 24 healthy male subjects. Subjects received 2 ng/kg Escherichia coli endotoxin (lipopolysaccharide) intravenously. Following experimental endotoxemia, endogenous adenosine concentrations increased. Expression of 5'ectonucleotidase messenger RNA was upregulated (p = .01), whereas adenosine deaminase messenger RNA was downregulated (p = .02). Furthermore, both adenosine deaminase and adenosine kinase activity was significantly diminished (both p ≤ .0001). A2a and A2b receptor messenger RNA expression was elevated (p = .02 and p = .04, respectively), whereas messenger RNA expression of A1 and A3 receptors was reduced (both, p = .03). In vitro, lipopolysaccharide dose-dependently attenuated the activity of both adenosine deaminase and adenosine kinase (both p ≤ .0001). Adenosine metabolism and signaling undergo adaptive changes during human experimental endotoxemia promoting higher levels of adenosine thereby facilitating its inflammatory signaling.